The Impact of Customized Interventions on Antenatal Mothers’ Body Mass Index - G Sathiyabama; S Kalabarathi; Nidhisharma (Journal of Pharmacy and Bioallied Sciences)
Introduction: Antenatal exercise andYoga improves strength, balance and flexibility and reduces maternal stress and yield better outcome of pregnancy. Aim: To assess and compare effect of yoga nad exercise on maternal Body mass Index Material and methods Sample size 132 and each group 33 samples one control and 3 experimental group. The YG and EG groups received prenatal exercise 40 minutes and yoga 20 minutes intervention 2 days per week consecutively 16 weeks provided. At 20th week the Pre test BMI and 36 week post test Measured. Results: Control group gradually improved BMI comparing to all Experimental groups, Significantly at P.0.001 level. The mean difference is significant at the 0.05 level. Conclusion: Customized yoga and prenatal exercise interventions will be more helpful in bringing BMI back to normal.